The bunionette deformity—evaluation and management - Cooper, Minton Truitt; Granadillo, Victor Anciano; Coughlin, Michael J. (Annals of Joint; Vol 5 (January 2020): Annals of Joint, 2019)
Bunionette refers to a painful prominence of the lateral eminence of the fifth metatarsal head. Evaluation consists of careful physical and radiographic examination, focusing on the nature of the deformity as well as other concomitant foot and ankle pathology. Many patients may be managed conservatively with shoe modification alone. However, in some cases this is not successful and surgical intervention may be considered. Successful surgical outcome is strongly tied to correct assessment of the deformity. A variety of surgical techniques have been described, ranging from proximal 5th metatarsal osteotomies to exostectomy. The aim of this article is to provide an overview or evaluation and management of this common deformity.